Sources of the "Diccionario gallego-castellano" (1913-1928) of the Real Academia Galega: Xoán Manuel Pintos, Eduardo Pondal, Benito Vicente Payzal - Sánchez Vales, Mª Dolores (Madrygal. Revista de Estudios Gallegos, 2013)
During the preparation of the first dictionary of the Real Academia Galega, which only reached to the word “cativo”, a lot of different lexical material was used, among it, the vocabularies of Xoán Manuel Pintos, Eduardo Pondal and Vicente Payzal. The way the information provided by these vocabularies was used, implicitly or explicitly, for the making of the dictionary, will help you to understand the laborious and complex process of writing this book.
Keywords: historical linguistics; lexicography; academic dictionary; Real Academia Galega